Management Strategies for Excellence Learning Programs in Realizing High-Achieving Students and High-Quality Madrasahs - Nasrullah (Formad English Foundation NTB-Jakarta, 2026)
Education in the contemporary era requires madrasahs to enhance both academic quality and institutional competitiveness while maintaining their religious identity. This study aimed to provide a comprehensive theoretical review of management strategies for excellence learning programs in realizing high-achieving students and high-quality madrasahs. This research employed a qualitative approach using a library research method with a theoretical review design. Data were collected from relevant scholarly books and peer-reviewed journal articles published within the last ten years through systematic literature search and documentation. The data were analyzed using qualitative content analysis, involving processes of data reduction, categorization, and thematic interpretation to identify key patterns and relationships. The findings revealed that effective management strategies are grounded in the integration of educational management, Total Quality Management (TQM), leadership, innovation, and collaborative approaches. These integrated strategies contribute significantly to improving students’ academic achievement through structured programs, research-based learning, and data-driven evaluation. In addition, they support the holistic development of students’ competencies and character through the integration of cognitive, affective, and spiritual dimensions. Furthermore, integrated management approaches enhance madrasah quality by aligning management functions, strengthening leadership and organizational culture, implementing continuous quality improvement, and adopting digital transformation. In conclusion, the study highlights that a holistic and integrated management framework is essential for achieving sustainable student achievement and institutional excellence in madrasahs. The findings provide both theoretical contributions and practical implications for strengthening educational management in Islamic institutions.